The significance of islamic value on ethics in corporate culture - Kamaliah, Salleh; Noor ‘Ashikin, Hamid; Noraida, Harun; Asiah, Bidin; Mohd Fuad, Husaini; Ahmad Zahid, Salleh (2018)
Islam is a religion which offers a complete guidance and rule to regulate our life. To meet this objective, Islam introduces the detailed concept of social and ethical behaviour for us to live with and apply for our personal as well as reference in business practice which can be adopted by commercial institutions and corporate organizations. Ethics are deemed to be vital in order to measure managerial competence and governance in corporate world nowadays. Various codes on Corporate Governance has since been developed through years and gone through numbers of review in order to enhance business ethics and practice. In Malaysia for example, the Malaysia Code on Corporate Governance has recently been reviewed in 2017 to promote greater internalisation of ethics into the corporate governance culture. This study aims primarily to explore the significance of Islamic value on ethics in the corporate culture globally. The study is based on qualitative approach which employs library research method for data collection. The study analyses various texts such as books, journals, reports and code. The study reveals that there are numbers of authentic Islamic approach to ethics which are in line with the current corporate code with regard to ethics and governance which can be adopted in the business practice nowadays.